2022
DOI: 10.32598/shenakht.9.4.39
|View full text |Cite
|
Sign up to set email alerts
|

The effect of watching models of teaching physical activity on cognitive-motor components and physical competence among children

Abstract: Introduction: The increase in immobility in all sections of society, especially children and adolescents, has become one of the most important concerns in the health status of this age group. Aim: The main purpose of this study was to investigate the effect of watching models of teaching physical activity on cognitive-motor components and physical competence among children. Method: The current research was a semi-experimental study with two experimental and control groups. The statistical population included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, the literature often cites studies that reflect the relationship between physical activity and the cognitive abilities of schoolchildren. The authors emphasize that physical activity has a positive effect on cognitive processes [37][38][39][40] and even the creative abilities of students [41].…”
Section: Resultsmentioning
confidence: 98%
“…Also, the literature often cites studies that reflect the relationship between physical activity and the cognitive abilities of schoolchildren. The authors emphasize that physical activity has a positive effect on cognitive processes [37][38][39][40] and even the creative abilities of students [41].…”
Section: Resultsmentioning
confidence: 98%
“…This is important because in some studies the authors show the relationship between physical exercise and cognitive functions of students. The opinion of several experts has shown that physical exercises have a positive effect on mental and cognitive functions (Bidzan-Bluma and Lipowska, 2018;Gao et al, 2018;Padulo et al, 2019;Sadeghi et al, 2022) and creative qualities (Piya-Amornphan et al, 2020) of children.The memory indicators of school children in the experimental group, namely, an increase in data of the study by 25.1% and 26.2% allows us to conclude that prolonged running has a positive and significant effect on the memory indicators of students.…”
mentioning
confidence: 99%